Current status, challenges, and policy suggestions for coalbed methane industry development in China: A review. Issue 4 (17th May 2019) - Tao, Shu; Chen, Shida; Pan, Zhejun
Abstract: China is vigorously promoting the development of coalbed methane (CBM) resources because CBM is cleaner than coal and a hazardous gas in coal mining. However, the CBM production in China is significantly lower than that in other coal‐rich countries, such as Australia and the United States. In this paper, the main problems hindering CBM development in China are discussed to provide management suggestions for the government. These key problems include exploration and development techniques, the overlap of mining rights, management, financial supporting policy, investment environment, regulations, and market conditions. The results of this study indicate that to improve the development of the CBM industry in China, national and local governments must enact specific and exercisable regulations to increase financial support, improve technology, increase investment in CBM exploration, strengthen public project establishment, and improve the reform of CBM exploration and development policies. Abstract : In this paper, the main problems hindering CBM development in China are discussed to provide management suggestions for the government. These key problems include exploration and development techniques, the overlap of mining rights, management, financial supporting policy, investment environment, regulations, and market conditions.